Algoneurodystrophy in a Patient with Major Depressive Disorder - Henriques, Virgínia; Henriques, Sérgio (Case Reports in Psychiatry, 2021)
Introduction. Not infrequently, in patients with a psychiatric illness who have concomitant physical symptoms, these symptoms are often wrongly attributed to a psychiatric illness. Consequently, there is a delay in establishing the correct diagnosis, which may have an impact on the prognosis of the disease. The authors aim to present a case report of a patient with a diagnosis of major depressive disorder and conversion disorder that was later correctly diagnosed with algoneurodystrophy. The authors intend to draw attention to the importance of a careful medical history and this entity. Case Presentation. A patient went to the emergency department multiple times with complaints of decreased strength and pain in the right upper limb, concomitantly with depressive symptoms. The patient was first diagnosed with conversion disorder and major depressive disorder. After the worsening of the clinical condition with the appearance of neuropathic pain and the exclusion of other organic pathologies, the probable diagnosis of algoneurodystrophy was made. At that time, the patient started treatment and a favorable clinical evolution was observed. Discussion. The clinical case highlights the importance of conducting a careful medical history in a patient with a psychiatric illness, so as not to mistakenly exclude the presence of an organic disease. The absence or delay in making a correct diagnosis can have adverse consequences in terms of the prognosis of the disease.